Development and validation of scale to measure the knowledge of Filipino barangay nutrition scholars on infant and young child feeding counseling - Sacdalan-Africa, Leila (Journal of Human Ecology, 2017)
The Barangay (Village) Nutrition Scholars (BNS) has been trained to do infant and young child feeding (IYCF) counseling but the absence of a validated knowledge test instrument limited the practice of knowledge assessment and pose question if they know the correct information for their client. The purpose of the study was to develop a psychometrically sound measure for BNS knowledge assessment on IYCF counseling. True or false, fill-in-the blanks and multiple-choice items were developed based on the training manual on IYCF counseling and other existing pre-and post-tests about this subject. An instrument with 38 items was pilot tested by a sample of 320 BNS. The item was increased to 47 through item analysis and was field-tested by a sample of 280 BNS. Exploratory factor analysis (EFA) using the pilot test data identified a two-factor model and 20 acceptable items for measuring recall and understanding. Confirmatory factor analysis (CFA) using the field test data supported a two-factor model (X2 (89) =97; p=0.27) but only with 15 acceptable items. Content validation using the study blue print necessitated the addition of seven meaningful items. Validity indices were adequate while internal consistency was desirable based on final analysis. The scale to measure knowledge of BNS in IYCF counseling is psychometrically sound and could be used to provide better judgments and explanation about the effectiveness of IYCF training and counseling, respectively.